Women and Artisanal Mining: Tin Mine in Kulur Village, Bangka Tengah - Sulista (Future Science)
Recently, the existence and participation of women are often not accommodated by various discourses and norms in mining governance policies, even though they are exist in mining. Gender equality issues, as the 5th goal of the SDGs, led the mainstreaming of the women's role quality, especially on economic strengthening activities, which were often left behind by the hegemons of menfolks before. This article analyzes the participation of female tin miners and challenges their visibility in the artisanal tin mining in Pulau Bangka. The research was conducted through field observations and in-depth interviews with some female miners whose selected purposely in Kulur Village, Bangka Tengah. This study found that women were most involved in tin panning activities, namely activities wash the waste of tin processing, of which is the result of tin mining activities by male workers in Sakhan. The desire to gain complement income provides opportunities for women to be more dynamic in managing the family's economic activities that do not only depend on the husband's yield. This study also presenting a problematic matter about the weakness of social protection these vulnerable groups, completing the complexity studies of assessing protection for artisanal mining workers.